A pointwise growth estimate for analytic functions in tubes - Richard D. Carmichael; Elmer K. Hayashi (International Journal of Mathematics and Mathematical Sciences)
A class of analytic functions in tube domains TC=ℝn+iC in n-dimensional complex space, where C is an open connected cone in ℝn, which has been defined by V. S. Vladimirov is studied. We show that a previously obtained L2 growth estimate concerning these functions can be replaced by a pointwise growth estimate, and we obtain further new properties of these functions. Our analysis shows that these functions of Vladimirov are exactly the Hardy H2 class of functions corresponding to the tube TC.